2018
DOI: 10.4194/1303-2712-v18_1_12
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Asian green mussel (Pernaviridis) is a bivalve species with a high economic value. The waters surrounding the Malaysian state of Sabah hosts a wide range of geographically distributed populations of P. viridis whose population structure is unknown. This study was conducted to elucidate the genetic diversity and population structure of Asian green mussel from six sites located along the coastline of Sabah based on the mitochondrial DNA control region (D-loop). The complete D-loop sequences of 197 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Geological evidence suggests that the river systems of Sarawak were historically interconnected with most major river systems of Peninsular Malaysia via the Sunda River during Pleistocene glaciation (about 10000 years ago), thus allowing gene flow among these drainages (Kamarudin and Esa 2009). Gene flow from populations in the Straits of Malacca to those in Sarawak has been reported in several studies including Ryan and Esa (2006), Azhar and Hassan (2015), Samani et al (2016) and Lau et al (2018). Meanwhile, populations of SN-KN, which are separated by the South China Sea, showed high genetic connectivity (pairwise F ST = 0.0702).…”
Section: Genetic Structurementioning
confidence: 89%
“…Geological evidence suggests that the river systems of Sarawak were historically interconnected with most major river systems of Peninsular Malaysia via the Sunda River during Pleistocene glaciation (about 10000 years ago), thus allowing gene flow among these drainages (Kamarudin and Esa 2009). Gene flow from populations in the Straits of Malacca to those in Sarawak has been reported in several studies including Ryan and Esa (2006), Azhar and Hassan (2015), Samani et al (2016) and Lau et al (2018). Meanwhile, populations of SN-KN, which are separated by the South China Sea, showed high genetic connectivity (pairwise F ST = 0.0702).…”
Section: Genetic Structurementioning
confidence: 89%
“…However, in the ATPase 6/8 analysis, H17 was clustered with an outgroup species, and one probable explanation is that H17 underwent a distinct mutational history. Nevertheless, the mitochondrial D-loop region generated more mutations and genetic variation than the ATPase region as reported in earlier studies (Mandal et al, 2012;Lau et al, 2018). Mutation rates in the D-loop and ATPase regions are different in different river populations; therefore, it is logical to analyze genetic diversity using multiple mitochondrial sequences.…”
Section: Discussionmentioning
confidence: 91%
“…This also indicates that other river populations might have experienced a population bottleneck followed by a rapid population growth (Bowen et al, 2001;Meng et al, 2015). The mismatch distribution and neutral test analysis helps us to investigate demographic history (Guo et al, 2014;Lau et al, 2018). Tajima's D value of low significance indicates that a population is deviating from the neutral expectations, and negative F s values signify deviation from neutrality, which may be due to the effect of population expansion and/or selection.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the genetic diversity of the five populations was high which indicated that the germplasm resources were in a good level. Such is the case in other shellfish populations, such as Donax vittatus (Fernandez-Perez, et al, 2017), Mytilus coruscus (Liu et al, 2019), and Perna viridis (Lau et al, 2018). The genetic diversity level is correlated with the effective population size; that is, the larger the effective population size, the greater the genetic contribution of the parents and the greater the selective response will be.…”
Section: Population Haplotype Distribution and Genetic Diversitymentioning
confidence: 94%